Synthesis and characterization of cellulose fibers cloths for tissue engineering - Nurul Nadirah, Suteris (2021)
Cellulose belongs to the class of renewable material as they can be produced from many plant-related resources and has received tremendous attention in recent time for reducing the environmental burden from mining for functional materials as well to decrease carbon footprint. Cellulose from empty fruit bunch (EFB) of oil palm plantation is developing into scaffolds to widen their application in skin tissue engineering as it can imitate the structure of extracellular matrix (ECM) that functions for proliferation, differentiation and attachment of the cells. Cellulose acetate (CA) is a cellulose derivative, one of the natural polymers that can easily be used to produce fiber scaffolds. The main objective of this research is to fabricate fiber scaffolds based on CA for skin tissue engineering applications by electrospinning technique. The studies can be categorized into two main parts. The first part focuses on fabricating the fiber mats of CA using electrospinning method and the second part is the characterization of the scaffolds via FESEM, ATRFTIR, TGA, XRD, contact angle and MTT assay to evaluate the performance of the scaffolds. Firstly, CA powder were dissolved in a blend of acetic acid and acetone. Then, the concentration of CA (13%) with poly(ε-caprolactone) (PCL) (15%) was prepared and mixed in different ratios (90%) of CA content and electrospun to obtain smooth and beadfree fiber scaffolds. The ATR-FTIR results showed that the interactions between functional groups of CA and PCL in the mixtures. Next, all the TGA curves showed similar trends means that all the scaffolds had similar amount of component were decomposed. The hydrophilicity enhancements are related to the hydrogen bonding between the components. The improved hydrophilicity contributed to improved swelling of the scaffolds; the PCL/CA/Cur (0.5%) and the PCL/CA/Cur (1.0%) showed swelling of ~700 and 950%, respectively, in PBS. The drug-release studies showed the highest cumulative drug release of 60% and 78% for PCL/CA/Cur (0.5%) and PCL/CA/Cur (1.0%) fiber, respectively. The second part of the research focused on the cytotoxicity studies of the cell proliferation and surface morphology of the fiber scaffolds based on MTT assays. The in-vitro studies showed that PCL/CA/Cur (0.5 wt.%) and PCL/CA/Cur (1.0 wt.%) fiber scaffolds facilitate a higher proliferation of fibroblast cells than other scaffolds without curcumin with 223.46% and 309.21% respectively. This demonstrated that the scaffolds with curcumin content was nontoxic and biocompatible to initiate the cell proliferation for repairing broken tissues.